(untitled) (Konturen, 2010)
In this essay the first initiatives are presented to come to a new theoretical approach of musical improvisation. The main idea is to regard musical improvisation as a nonlinear dynamical system in which various (f)actors interact and connect in complex ways. In other words, the Field of Musical Improvisation (FMI) has no stable or strict identity.